Multiple watermarking technique based on RDWT-SVD and human visual characteristics - Noruhida, Alias; Ernawan, F. (JATIT, 2019)
With the increasing multimedia technology, digital watermarking technique is needed for copyright protection. The multiple watermarking technique is required for embedding more than one watermarks. A major challenge needs to be solved specially to recover multiple watermarks that may be destroyed due to JPEG compression. This paper proposed multiple embedding techniques for watermarks based on RDWT-SVD and human visual characteristics. The proposed scheme examines U(2,1) and U(3,1) components of RDWT-SVD. Our scheme uses Arnold transform to scramble the watermarks before embedding watermarks into the host image. The proposed scheme is tested under several attacks such as image compression, geometrical and image processing attacks. The experimental results show that our scheme can achieve a higher robustness for both recovered watermarks than the existing technique. Our scheme produces high robustness with the normalized-cross-correlation about 0.99 under noise additions. Â© 2005 â ongoing JATIT & LLS.